Computational fluid dynamic (CFD) of vertical-axis wind turbine: Mesh and time-step sensitivity study - Ashwindran, S.; Azizuddin, Abd Aziz; Oumer, A. N. (Penerbit UMP, 2019)
This paper presents mesh and time-step dependence study of newly designed drag type vertical axis wind turbine. Ansys FLUENT a commercially available CFD solver was used to perform CFD numerical study on the drag type wind turbine. In computational analysis, 2D models was simulated under unsteady flow fields using SST k-ω to achieve stabilized numerical convergence. The model was analyzed at static and dynamic mode, where sliding mesh technique was used to analyze the turbine in dynamic mode. Three main parameters were taken under careful consideration: mesh resolution, turbulence model and time-step. Aerodynamic force was used in mesh sensitivity study for both static and sliding mesh. A small discrepancy in results of 2D sliding mesh result at different time-step and mesh resolution was observed. The generated results showed good agreement between fine and medium mesh with small difference in the initial initialization. In time-step dependency study for static mesh, dt=0.0002 time-step size was chosen for economical computational cost.